OBITUARY : MISS ELIZABETH CARTWRIGHT - O’Dowd, Clodagh (Akroterion, 2014)
During her 38 years as Latin teacher at Rustenburg Girls’ High School, Miss Elizabeth Cartwright gained the love and respect of the many generations of pupils who passed through her hands.